1998
DOI: 10.1093/jn/128.9.1525
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Infusions of Palmitic, Stearic or Oleic Acids Differently Affect Mammary Gland Metabolism of Fatty Acids in Lactating Dairy Cows

Abstract: The effect of dietary lipids on the fatty acid (FA) profile of cows' milk fat is mainly dependent on digestive processes and mammary gland uptake and metabolism of FA. The objective of this study was to determine the separate effects of high arterial concentrations of 16:0, 18:0 and cis-18:1(n-9) on uptake, synthesis and 18:0 desaturation rate in the mammary gland of lactating dairy cows, via arterio-venous differences and mammary gland balance of FA. In a 4 x 4 Latin square, four lactating Holstein cows with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
81
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 38 publications
14
81
0
7
Order By: Relevance
“…This can be explained by an increased intake of cis-9 18:1, and also due to increased mammary availability of 18:0, which is desaturated at the mammary gland level. Around 50% of 18:0 taken up by the mammary gland is desaturated (Enjalbert et al, 1998), and all studies examining responses to supplemental rapeseeds or rapeseed oil in the diet report an increase in milk cis-9 18:1 concentration (Givens and Shingfield, 2006;Glasser et al, 2008). Increases in milk fat cis-9 18:1 concentrations to both rapeseeds were linear across the range of supplements fed in this experiment, indicating the potential to further enhance milk cis-9 18:1 content.…”
Section: Kliem Shingfield Humphries and Givensmentioning
confidence: 59%
“…This can be explained by an increased intake of cis-9 18:1, and also due to increased mammary availability of 18:0, which is desaturated at the mammary gland level. Around 50% of 18:0 taken up by the mammary gland is desaturated (Enjalbert et al, 1998), and all studies examining responses to supplemental rapeseeds or rapeseed oil in the diet report an increase in milk cis-9 18:1 concentration (Givens and Shingfield, 2006;Glasser et al, 2008). Increases in milk fat cis-9 18:1 concentrations to both rapeseeds were linear across the range of supplements fed in this experiment, indicating the potential to further enhance milk cis-9 18:1 content.…”
Section: Kliem Shingfield Humphries and Givensmentioning
confidence: 59%
“…This would lead to a lower rumen outflow of 18:0 and reduced mammary desaturation to cis-9 18:1 (as described by Kinsella, 1972). Enjalbert et al (1998) found that there was a negative relationship between arterial circulation of trans-18:1 isomers and 18:0 desaturation in the mammary gland. However, when taking into account desaturation ratios (by dividing cis-9 10:1 by 10:0 and cis-9 14:1 by 14:0), there was no difference in desaturation activity for each of the diets, possibly due to low variations of circulating trans-18:1 isomers in the blood between diets.…”
Section: --mentioning
confidence: 83%
“…NEFA uptake is directly related to their plasma concentration, which is itself mainly related to body fat mobilisation [29]. The ability of mammary tissue to utilise triglyceride FA from plasma lipoproteins is determined by the activity of the enzyme lipoprotein lipase than 50% of the oleic acid that is secreted into milk fat [16,57]. Furthermore, vaccenic acid (trans-11 C18:1) formed in the rumen and absorbed from the intestine can be desaturated to form rumenic acid, i.e.…”
Section: Mammary Lipid Synthesismentioning
confidence: 99%